Bergamot extract and red yeast rice in reducing high cholesterol - what is known? - Justyna Składanek; Michał Leśkiewicz; Barbara Kopczyńska (Nicolaus Copernicus University in Toruń, 2024)
Obtaining optimal levels of lipoproteins and total cholesterol is one of the main goals for reducing cardiovascular risk. Many patients insist on changing their statin treatment to a nutraceutical such as Bergamot extract or red yeast rice extract, due to statin intolerance affecting some of them and increasing disinformation on statin side effects. This is why, interest in lipid-lowering ability of available nutraceuticals, is growing. In our work, we tried to summarise what is known about nutraceuticals such as red yeast rice and bergamot extract and how they can be used in clinical practise. We searched two databases such us Pubmed and Medline byusing the terms "bergamot", "red yeast rice", "dyslipidaemia" and "hypercholesterolaemia" Products containing red yeast rice and bergamot extract are dietary supplements which are sold over the counter. There is possibility that they can be seen as natural substances which significantly reduce cholesterol levels, however, they have weaker effect than strong statins. They cannot be replacement for them. Red yeast rice is the leading substance. It can be used in patients with moderate hypercholesterolemia or can be combined with ezetimibe if statins are badly tolerated. There is no clear opinion of experts on bergamot due to lack of larger and longer studies. As our article show it is crucial to conduct more scientific research on nutraceuticals especially Bergamot extract.